Diversity in the usages of edible wild plants by the Baka and Bakwélé in the periphery of the Tala Tala Forest Management Unit, North Congo - Betti, Jean Lagarde; Kourogue, Rosine Liliane; Achuo Mbong, Faustine; Billong Fils, Pascal Eric; Njimbam Njukouyou, Oumar Farick (Ethnobotany Research and Applications, 2020)
Background: In practice, timber companies use production forests or forest management units (FMU) for timber/wood purposes. Little attention is paid for Non-wood forest products (NWFP), which is not good. This study analyses the diversity in the usage of edible wild plants among the people based in the periphery of the Tala Tala FMU in the North Congo. Methods: An ethnobotanical survey was conducted from 8 to 23 May 2012 on edible NWFP used by Baka and Bakwele populations living in the periphery of the Tala Tala FMU. The method used is the one called «Method for the popular usage», which consists of gathering data on the popular use of forest products in a given area. By comparing the Tala Tala whole population to a forest zone, it is possible to make reconciliations between the systematic botany and the ethnobotany. This reconciliation distinguishes five levels of data collection in the ethnobotany of the Tala Tala including the whole population, the ethnic group, the informant (household), the plant species, and the quotation. We assessed the relative importance, diversity, and similarities in the usages of edible NWFP. Results: A total of 52 households provided information on the popular use of wild edible plants. A total of 57 plant species and 69 recipes were collected for which a total of 594 quotations (citations) were made. These plant species are distributed in 46 genus and 33 families. The Baka and Bakwélé communities use the same plant species and recipes in the same way and with the same importance. The overall usage diversity is higher for both plants and recipes (H>4, E>0.8) among Baka pygmies than Bakwélé people. Conclusions: Some plants used in the Tala Tala FMU are well known in other Congo basin countries for similar usages. Other were identified as ‘’priority’’ or ‘’key’’ edible NWFP. The glaring development challenge of what precedes is the urgent need to assess the abundance (availability) and conduct a structural analysis of the plant species used with the view to propose fair management schemes. Keywords: Forest Management Unit, Non-Wood Forest Products, edible plants, recipes, ethnobotany, diversity indexes.